Research Progress of Pyroptosis in Alzheimer’s Disease - Xue, Weiyue; Cui, Di; Qiu, Ye (Frontiers in Molecular Neuroscience, 2022)
Alzheimer's disease (AD) is a disease characterized by insidious and progressive neurodegeneration, with clinical syndromes of memory and visuospatial skills damage. The pathogenic mechanism of AD is complex in which neural inflammation and neuron death play important roles. Pyroptosis, an inflammatory programmed cell death, has been reported to be involved in neuron death. Pyroptosis is executed by the protein family of gasdermins which punch pores on plasma membrane when activated by the upstream signals including the activation of NLRP3 and caspases, and subsequently triggers the inflammatory cascades featured by the release of interleukin (IL) -1β and IL-18. Herein, we summarized the current research on the roles of neuron pyroptosis in AD, aiming to provide a comprehensive view of the molecular mechanisms underlying AD pathogenesis and potential therapeutic targets for AD.